An analysis of local perceptions of the role of drought in exacerbating contemporary pastoral conflict in northern Kenya: a case study of Marsabit County - Mohamed, Bishar (Department of Environmental and Geographical Science, 2019)
Pastoralists’ communities in Kenya have been co-existed since their migration and settlement in the region. However, frequent conflicts have been experienced among these communities due to scarcity of natural resources and drought. Pastoralists in Kenya are concern with raising their livestock, moving the herds in search of scarce resources such as water and pasture. The root cause of pastoralist conflict in Kenya is scarcity of natural resources and drought. This has often been suggested to trigger conflict flare-ups and that there was a recent flare up in the year 2016. Many descriptions of the conflict suggest that drought is an underlying driver, however other factors have also been suggested, i.e., politics, availability of arms, cultural values, population, governance, and lack of income (Adano et al., 201. Hence this research project explores the local perceptions of the main drivers of conflict. While studies have been conducted on the effects of droughts on pastoral communities and their coping strategies in the County, little is known of the perceptions of the locals on the role of drought in exacerbating inter-ethnic violence among three main pastoral communities in the region i.e. Borana, Gabra and Rendille. The main objective of this study was to establish the local perceptions of drought in exacerbating contemporary pastoral conflict in Marsabit County. Though there have been several studies on vulnerability to drought conducted in the area, all of them tend to neglect the conflict between the three main clans in Marsabit County. Moreover, the pastoralist communities in the region have experienced conflict flare-ups for many years despite availability of institutions that ought to have solved it. Therefore, the study specifically aims to analyze the different causes of conflict in Northern Kenya with an eye to determine the perceptions of Borana, Burji and Rendille clans and government and non-governmental on role of drought in increasing conflict in the Marsabit County. The study also examines different interventions used by government and non-governmental organizations in dealing with conflict in the area. The population of the study comprised 100 randomly selected community members from nine villages in Marsabit County and 15 government and non-governmental employees in Marsabit County. The study draws on data gathered through a questionnaire designed to meet the objectives of the study. The quantitative data was coded, processed and summarized into frequencies, percentages and graphs. The qualitative information from the interview is narrated as a report. In the questionnaire presented to participants, the extent to which each factor contributes to the conflict in the region is given in numerical categories i.e. (4-5) meaning agreed to a very high extent, (3) moderate extent or unsure and (1-2) agree to a very low extent or not at all. The study found that both locals and NGOs in the region perceive scarcity of resources which leads to drought as the main factor that influences the conflict in the region as compared to other factors i.e. cultural values, politics, population increase and cultural values. According to respondents, the drought caused a deficiency in natural resources i.e. water and pasture, which contributed to the conflict to a great extent. The study also found that locals in Marsabit County perceived different factors such as poverty, politics and cultural resources as influencing interethnic conflict in the region. The study recommends the following-: - There is need for the government and other non-governmental organizations to come up with more strategic ideas for climate change adaptation, ideas that could go hand in hand with the changing environment. - There is also a need to broaden and spread the livelihood and entrepreneurship projects to all the sub-counties where the climate change impact is harsh. - The county government needs to increase its budget allocation for pastoralist communities. This will promote sustainable development and create more jobs for the youths in the county. - County government, politicians and community elders should come up with a clear approach to tackle conflict in the region and prosecute the perpetrators of inter-ethnic conflict in the region.